LYW-6, a novel cryptotanshinone derived STAT3 targeting inhibitor, suppresses colorectal cancer growth and metastasis. (March 2020) - Wang, Huan; Liu, Zhe; Guan, Lingnan; Li, Jiankang; Chen, Siyi; Yu, Wenying; Lai, Maode
Graphical abstract: Highlights: LYW-6 is a new derivative of natural product cryptotanshinone with high potency on STAT3 inhibition. LYW-6 directly binds to STAT3 protein with high affinity. LYW-6 attenuates the growth and metastasis of colorectal cancer in vitro and in vivo . Abstract: The constitutive activation of signal transducer and activator of transcription 3(STAT3) is associated with aggressive development and metastasis in colorectal cancer (CRC), but STAT3-targeting drugs remain elusive in clinic. Here, structure-based strategy was used to remodel the natural compound cryptotanshinone into a more effective STAT3 inhibitor LYW-6. Using the Biolayer Interferometry assay, we observed that LYW-6 exhibited specific interactions with STAT3(KD = 6.6 ± 0.7 μM). Western blot analysis and electrophoretic mobility shift assays (EMSA) showed that LYW-6 inhibited the phosphorylation of STAT3 tyrosine 705 (Tyr-705) and had slight effects on STAT1 and STAT5 phosphorylation. Western blot analysis on the upstream kinases of STAT3 confirmed that the inhibitory mechanism on p-STAT3 was independent of upstream kinases. Further investigation demonstrated that LYW-6 downregulated the expression of downstream oncogenes to inhibit cell viability, cell cycle development, and potently increased cell apoptosis in human CRC cells. The invasion and metastasis linked signaling was also blocked by LYW-6 treatment. LYW-6 was found to reduce the metastasis foci in lung on tail-lung metastasis models. In addition, it was observed that LYW-6 markedly diminished STAT3 phosphorylation in tumor tissue and significantly inhibited tumor growth on xenograft models. Tumor development on chemically-induced colorectal cancer model also significantly inhibited by LYW-6 treatment. These findings provided adequate evidence that STAT3 inhibitor LYW-6 might be a potential candidate agent for CRC treatment.